The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.mce.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of genetic alterations in adrenocortical tumorigenesis

Abstract: Whereas benign adrenocortical tumors are frequent in the population, adrenocortical carcinoma (ACC) is a rare cancer. Significant advances in the understanding of the pathogenesis of sporadic ACCs have been possible through the study of hereditary syndromes responsible for ACCs. The genetic alterations involved in these syndromes have also been found in sporadic ACCs. Several specific genes have been shown to be altered in sporadic ACCs. Despite these progresses, the underlying sequence(s) of events remains( )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
6
0
2
Order By: Relevance
“…Development of adrenocortical carcinoma is not well characterised. Comparative hybridisation studies and allelotyping have shown that the number of genetic alterations increases with tumour size as a sign of an overall altered genetic stability in the malignant tumours (4,5,9). The most common genetic aberrations are gains on chromosome 4 and 5 and losses on chromosome 11 and 17.…”
Section: Introductionmentioning
confidence: 99%
“…Development of adrenocortical carcinoma is not well characterised. Comparative hybridisation studies and allelotyping have shown that the number of genetic alterations increases with tumour size as a sign of an overall altered genetic stability in the malignant tumours (4,5,9). The most common genetic aberrations are gains on chromosome 4 and 5 and losses on chromosome 11 and 17.…”
Section: Introductionmentioning
confidence: 99%
“…The H19 gene is located in 11p15 locus , the same region of insulin-like growth factor-2 ( IGF2 ) gene. The H19 expression is downregulated in Beckwith-Wiedemann syndrome and is inversely related to IGF2 [46]. To date, distinct studies reported miRNA expression profile in adults and one in pediatric adrenocortical tumors.…”
Section: Microrna Expression In Adrenocortical Tumorsmentioning
confidence: 99%
“…ACC develops in approximately 3–4% of patients with Li–Fraumeni syndrome, usually manifesting before the age of 20 years 12. In addition, inactivating somatic mutations in the TP53 gene have also been observed in sporadic ACC in 20–33% in exons 5–8 12, 13 and in 25% in exons 2–11 12. In addition, a substitution of histidine for arginine at codon 337 has been shown in the development of childhood ACC in 1 in 10 carriers of this missense mutation 12.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a substitution of histidine for arginine at codon 337 has been shown in the development of childhood ACC in 1 in 10 carriers of this missense mutation 12. The outcome of the resulting mutation is the inability of the p53 protein to initiate cell growth arrest, DNA repair and apoptosis in response to severe cellular DNA damage 13. Li–Fraumeni syndrome is also characterized by the development of soft tissue sarcomas, osteosarcomas, breast cancer, brain tumors, and leukemia at an early age.…”
Section: Introductionmentioning
confidence: 99%